Association between fetal sex and metabolic syndrome in women aged 40 years and older: the REACTION study - Xie,Qian; Li,Ruoqing; Wan,Qin; Tong,Nanwei (PeerJ, 2025)
Introduction This study aimed to investigate whether fetal sex influences the risk of metabolic syndrome (MetS) in women in China. Materials and Methods A cohort of 3,758 Chinese women, each having given birth to only one child and aged 40 years or older, was included in the study. Registry data on all pregnancies and miscarriages were collected for each participant. This retrospective cohort study aimed to determine whether fetal sex was associated with metabolic syndrome. MetS was defined as meeting at least three of the following five criteria: impaired insulin metabolism, reduced glucose tolerance, hypertension, dyslipidemia, and large waist circumference. Results Among the 3,758 women aged 40 years and older in Luzhou City, 1,018 (27.1%) developed MetS. Mothers who had carried a male fetus had higher triglyceride (TG) and total cholesterol (TC) levels and a greater prevalence of diabetes than those who had carried a female fetus (P < 0.05). Although the incidence of MetS was higher in women who had carried a male fetus than in those who had carried a female fetus, the difference was not statistically significant (P > 0.05). Notably, MetS was significantly less prevalent in premenopausal women than in postmenopausal women, irrespective of fetal sex (P < 0.05). In the postmenopausal subgroup, the incidence of MetS was significantly higher in women who had carried a male fetus compared to those who had carried a female fetus (P < 0.05). Conclusions Our study found no significant association between fetal sex and MetS in Chinese women aged 40 years and older. However, among postmenopausal women, the incidence of MetS was significantly higher in those who had carried a male fetus. Greater attention should be given to postmenopausal women with a history of carrying a male fetus, and early preventive measures should be implemented to reduce the risk of related chronic diseases.
Keywords: Fetal sex; Metabolic syndrome; Premenopausal; Postmenopausal; Diabetes